Lymphocyte antigen 6 complex locus G6D downregulation is a novel parameter for functional impairment of neutrophils in aged mice - Saito, Suguru; Okuno, Alato; Maekawa, Toshio; Kobayashi, Ryoki; Yamashita, Osamu; Tsujimura, Noriyuki; Inaba, Morihiko; Kageyama, Yasushi; Tsuji, Noriko M. (Frontiers in Immunology, 2022)
Immunological aging is a critical event that causes serious functional impairment in the innate immune system. However, the identification markers and parameters are still poorly understood in immunological aging of myeloid lineage cells. Here, we show that a down regulation of Lymphocyte antigen 6 complex locus G6D (Ly-6G) observed in aged mice neutrophils could serve as a novel marker for the prediction of age-associated functional impairment in the neutrophils. Ly-6G expression was significantly downregulated in the bone marrow (BM) and peripheral blood (PB) neutrophils of aged mice compared to young mice confirmed by flow cytometry analysis. In vitro experiments using BM-isolated neutrophils showed significant down regulations in there activities, such as phagocytosis, reactive oxygen species (ROS) production, interleukin (IL)-1β production, neutrophil extracellular traps (NETs) formation, and migration as well as bacterial clearance, in the aged mice neutrophils compared to those of young mice counterparts. Interestingly, the magnitudes of functional parameters were strongly correlated with the Ly-6G expression in the neutrophils. Thus, our results suggest that down regulation of Ly-6G reflects the age-associated functional attenuation of the neutrophils.